Функції художньої деталі в повісті Галини Триліс «Елішка» - Перцева, В. А.; Pertseva, V. А.; ORCID: http://orcid.org/0000-0002-5203-761X (Virtus: Scientific Journal. – 2020. – March (№ 42). – P. 131-135, 2020)
У статті проаналізовано місце художньої деталі у творчості Галини Триліс. Особливу увагу приділено вивченню типів художньої деталі, що формують образи головних героїнь повісті, а також виконують основну роль сюжетної побудови в досліджуваному творі письменниці.

This research is essentially the first attempt to show the peculiarities of artistic thinking of modern Ukrainian writer Galina Trylis. The purpose of the article is to study the artistic part as a stylistic dominant to the works of Trylis. External (subject, natural, portrait) and internal (psychological) types of details are analyzed. The artistic details that form the images of the main heroines of the story «Elishka», as well as the details underlying the spatial-time boundaries of the work are considered separately. The functions of artistic details in the works of Galina Trylis are defined.

В статье проанализировано место художественной детали в творчестве Галины Трилис. Особое внимание уделено изучению типов художественной детали, которые формируют образы главных героинь повести, а также выполняют основную роль сюжетного построения в исследуемом произведении писательницы.
Function of literary details in the story of Galina Trylis «Elashka»
Перцева В.А. Функції художньої деталі в повісті Галини Триліс "Елішка". Virtus: Scientific Journal, Іssue №42. 2020. С.131-135
Перцева, В. А. Функції художньої деталі в повісті Галини Триліс "Елішка" / В. А. Перцева // Virtus: Scientific Journal. – 2020. – March (№ 42). – P. 131-135.
Keywords: Мова. Мовознавство. Літературознавство. Language. Linguistics. History and Criticism of Literature. Язык. Языкознание. Литературоведение; художня деталь; художній текст; literary detail; literary text; structure; landscape; composition; portrait characteristics; interior; сюжет; композиція; психологічний аналіз; портретна характеристика; інтер’єр; пейзаж; художественная деталь; интерьер; композиция; художественный текст; психологический анализ; портретная характеристика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина